Temporal Variations of Petrological Characteristics of Tangkil and Rajabasa Volcanic Rocks, Indonesia - Hasibuan, Reza Firmansyah; Ohba, Tsukasa; Abdurrachman, Mirzam; Hoshide, Takashi (Indonesian Journal on Geoscience, 2020)
DOI:10.17014/ijog.7.2.135-159Tangkil and Rajabasa Volcanoes are neighbouring subduction-zone volcanoes located on the southeast tip of Sumatra Island (Sunda Strait, Indonesia). Stratigraphic correlation of lavas in Tangkil-Rajabasa volcanic area was established from field observations, morphological analysis, and K-Ar dating analysis. Detailed petrography and geochemical data of two and eleven lava units from Tangkil and Rajabasa, respectively, were then integrated with the stratigraphy to show the temporal variations. Early stage (> 4.3 Ma) effusives of Tangkil Volcano are dacitic to rhyolitic (67-71 wt. % SiO2; Tklf), whereas the later (c. 4.3 Ma) rocks are basalt to basaltic andesite (c. 52 wt. % SiO2; Tklm). Tangkil shows bimodal magmatism, of which the felsic endmember is > 71 wt. % SiO2 and < 0.1 wt. % MgO. Lavas of Rajabasa Volcano are comparatively younger (c. 0.3 to 0.1 Ma) with compositions ranging from basalt to andesite (51-62 wt. % SiO2; Rbs). Chemical variations of Rajabasa accounts for the interactions of at least three endmembers: Mg-rich medium-K basalt magma, low-Mg medium-K basalt magma, and high-K andesitic magma. During the long evolution of Rbs magma system, the temporal chemistry shows rising-falling variation in SiO2 and MgO indicating the three magmas were active. The felsic endmember magma of Rajabasa is fixed in composition (at ~62 wt. % SiO2; ~2.2 wt. % MgO). The rocks from the last Tklf and Rbs indicate open system processes by containing plagioclase and pyroxene phenocrysts that show resorption of evolved core and overgrowth of less evolved mantle. The multiple zones of dissolution-overgrowth in plagioclase crystals and the fluctuating trend in temporal whole-rock variation suggest that the changes of magmatic condition in temperature, H2O, or chemical composition were repetitive.